Danni the drum fairy - Meadows, Daisy (Meadows, Daisy. Music fairies, 2010)
Jack Frost and his goblins have stolen the Music Fairies' magic instruments. Music everywhere is out of tune! Now the goblins plan to play the instruments in a TV talent contest. If Rachel and Kirsty don't act fact, everyone could find out about Fairyland!